Weather Conditions and Warm Air Masses in Southern Sakha During Active Forest Fire Periods - Hayasaka, H.; Yamazaki, K.; Naito, D. (Fuji Technology Press Ltd., 2019)
Forest fires are a common and destructive natural disaster in Russia. Weather conditions during active forest fire periods in southern Sakha (Eastern Siberia) at high latitudes (58–65°N, 120–140°E) were evaluated. Periods of high fire activity during 2002 to 2016 were identified using MODIS (moderate resolution imaging spectroradiometer) hotspot data by considering the number of daily hotspots and their continuity. Weather conditions during the top seven periods of high fire activity were analyzed using atmospheric reanalysis data for upper (500 hPa) and lower levels (925 hPa). Our results showed that active fires occurred under varied weather conditions and it was difficult to find common weather patterns at both upper- and lower-levels during the seven most active fire periods. Furthermore, it was apparent that the northward movement of warm air masses (cTe: continental temperate) from lower latitudes (∼40°N) toward southern Sakha tended to exacerbate fires mainly due to strong wind conditions during the seven most active fire periods. In particular, on peak hotspot days, warm air masses from the south existed commonly near southern Sakha. This northward movement of warm air masses can be used to forecast fire and predict future fires in the region.